What is the appropriate initial management for a patient found to have a monoclonal gammopathy?. Issue 6 (June 2016) - Sakariya, Geetabahen; Hostetter, Jeff
Abstract : Evidence‐Based Answer : Initial management of a newly found monoclonal gammopathy (M‐protein) includes history, physical examination, and ancillary studies—complete blood count (CBC), serum calcium, serum creatinine, serum protein electrophoresis (SPEP), urine protein electrophoresis (UPEP), radiologic skeletal survey, and baseline bone densitometry (SOR: C, guidelines based on large observational studies and expert opinion). If monoclonal gammopathy of undetermined significance (MGUS) is diagnosed, then the kappa‐to‐lambda serum free light chain (SFLC) ratio and serum M‐protein level with IgA or IgM subtyping should be obtained to determine the risk for progression to malignant gammopathy (SOR: B, based on single high‐quality cohort study).